RELATIONSHIP MARKETING AS AN INNOVATIVE AND APPLIED CONCEPT FOR THE DEVELOPMENT OF AN ARCHITECTURAL AND CONSTRUCTION COMPANY - KUBANOV, Ruslan; KOPCHUK, Ivan; ZHOVKVA, Olha; MAKATORA, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the concept of relationship marketing as an innovative and applied strategy for the development of architectural and construction companies. The authors substantiate the relevance of this approach, driven by dynamic changes in the construction industry, intensifying global competition, evolving consumer preferences, and the advancement of digital technologies. The paper provides an in-depth analysis of the key components of relationship marketing, including co-creation of value, effective communication, long-term commitments, and mutual benefit. The authors emphasize that value co-creation enables companies to actively involve partners in the development of innovative solutions, thereby enhancing their competitiveness. Effective communication, built on trust and transparency, serves as the foundation for successful collaboration. Long-term commitments help reduce risks, improve planning, and ensure the effective implementation of joint projects. Mutual benefit motivates participants to continue developing their partnerships. The study also highlights practical aspects of implementing relationship marketing in architectural and construction companies. The authors stress the importance of a systemic approach that involves the development of specialized programs, the use of modern digital technologies to enhance interaction, and the formation of partnership ecosystems. Such initiatives enable companies not only to adapt to change but also to proactively influence trends in the industry. The results confirm that relationship marketing is a key element in ensuring competitiveness and sustainable development for architectural and construction companies. The implementation of this concept improves service quality, strengthens customer orientation, and creates the conditions for long-term market leadership. The authors highlight that in the context of global challenges and industry transformation, relationship marketing becomes a strategic imperative for the success of architectural and construction companies.
Keywords: relationship marketing; architectural and construction company; innovative development; value co-creation; effective communication; long-term commitments; mutual benefit; partnership ecosystems; customer orientation; transformation of the construction industry